A Director's Duty of Loyalty and the Relevance of the Company's Scope of Business: Cheng Wai Tao v Poon Ka Man Jason. Issue 5 (6th September 2017) - Koh, Pearlie
Abstract : The Hong Kong Court of Final Appeal has utilised a 'scope of business' inquiry to delineate the boundaries of the no‐conflict rule for the company director. Such an inquiry is directed at discerning the realistic ability of the company to exploit any particular business opportunity and a strict capacity approach is eschewed, at least where the no‐conflict rule is concerned. The decision is premised on a bifurcation between the no‐conflict and no‐profit rules, suggesting that the tests to determine breach of these fiduciary rules are not necessarily the same, thus permitting a more nuanced consideration of directorial breaches.